The Pseudomonas aeruginosa Secreted Protein PA3611 Promotes Bronchial Epithelial Cell Epithelial-Mesenchymal Transition via Integrin αvβ6-Mediated TGF-β1-Induced p38/NF-κB Pathway Activation - Shu, Lei; Chen, Sixia; Lin, Shaoqing; Lin, Huan; Shao, Yan; Yao, Jing; Qu, Lili; Zhang, Yunshi; Liu, Xing; Du, Xingran; Deng, Kaili; Chen, Xiaolin; et al. (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa (PA) is an important pathogen that has been proven to colonize and cause infection in the respiratory tract of patients with structural lung diseases and to lead to bronchial fibrosis. The development of pulmonary fibrosis is a complication of PA colonization of the airway, resulting from repeated infection, damage and repair of the epithelium. Bronchial epithelial cell epithelial−mesenchymal transition (EMT) plays a vital role in bronchial fibrosis. To date, research on bronchial epithelial cell EMT caused by PA secreted virulence factors has not been reported. Here, we found that PA3611 protein stimulation induced bronchial epithelial cell EMT with mesenchymal cell marker upregulation and epithelial cell marker downregulation. Moreover, integrin αvβ6 expression and TGF-β1 secretion were markedly increased, and p38 MAPK phosphorylation and NF-κB p65 subunit phosphorylation were markedly enhanced. Further research revealed that PA3611 promoted EMT via integrin αvβ6-mediated TGF-β1-induced p38/NF-κB pathway activation. The function of PA3611 was also veriﬁed in PA-infected rats, and the results showed that ΔPA3611 reduced lung inflammation and EMT. Overall, our results revealed that PA3611 promoted EMT via integrin αvβ6-mediated TGF-β1-induced p38/NF-κB pathway activation, suggesting that PA3611 acts as a crucial virulence factor in bronchial epithelial cell EMT and is a potential target for the clinical treatment of bronchial EMT and fibrosis caused by chronic PA infection.